Well-Being and Quality of Life - Medical Perspective 2017
DOI: 10.5772/67742
|View full text |Cite
|
Sign up to set email alerts
|

How Air Pollution Affects Subjective Well-Being

Abstract: Clean air is considered as one of the basic requirements for human being. Pollution-related diseases due to air pollution continue to rise at an alarming rate and affect people's quality of life. Air pollution also adversely affects welfare inequality. Air pollution as a significant risk factor affects health and sense of subjective well-being (SWB). In this study, the effect of air pollution on subjective well-being (life satisfaction, happiness, and optimism) is investigated. Relationship between well-being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…Nonetheless, I found no association between the neighborhood scale of air pollution and noise and GLS. This finding confirms those of Urban and Máca (2013) and runs counter to Orru et al (2016) and Darçın (2017), who found such an association among the general population. Comparisons across studies, however, should be made with caution for several reasons.…”
Section: Discussionsupporting
confidence: 84%
“…Nonetheless, I found no association between the neighborhood scale of air pollution and noise and GLS. This finding confirms those of Urban and Máca (2013) and runs counter to Orru et al (2016) and Darçın (2017), who found such an association among the general population. Comparisons across studies, however, should be made with caution for several reasons.…”
Section: Discussionsupporting
confidence: 84%
“…In the developed world, rural areas have much lower QoL than urban areas [ 26 ]. This could be true for developing countries, but a high population density and pollution levels in the urban areas might also negatively affect the subjective QoL in these regions [ 27 ]. Besides, a lack of green space can trigger a decline in health in urban areas [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could be true for developing countries, but a high population density and pollution levels in the urban areas might also negatively affect the subjective QoL in these regions [ 27 ]. Besides, a lack of green space can trigger a decline in health in urban areas [ 27 ]. This also makes sense when we consider that our subjects recovered from a highly infectious airborne respiratory disease.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with previous study conducted by Hawlader et al in Bangladesh ( 18 ). In urban areas, high population density and pollution levels may also have a negative impact on subjective QOL ( 42 ).…”
Section: Discussionmentioning
confidence: 99%